Integration of a photonic crystal fibre to a solid fibre - Hee, Zhi Sheng (2018)
The proliferation of fibre optics has been observed in the last few decades, from replacing copper wires for long distance information transfer to novel applications like guiding sunlight into enclosed areas in the day or advance sensing applications. There are many types of fibre designs from Single Mode fibres (SMF) to Multi-mode fibres and even exotic micro-structured fibres such as Photonic Crystal fibres (PCF). SMF is simple, efficient at propagating light and cheap. It uses the differences in refractive index between the core and cladding to propagate light through total internal reflection. Micro-structure fibre such as PCF has a complex structure and is able to handle high power application and possess special properties that are dependent on design. It is able to guide light primarily in 2 manners. First through difference in refractive indexes and second through arranging holes in a way that scattered light is guided through constructive interference. SMF is by far the most popular and widely used type of fibre due to its telecommunication applications and therefore much commercial equipment are designed for SMF. PCF researches is getting increasingly popular and have the potential to have very sensitive and accurate sensing or high powered applications such as fibre lasers. The large degree of freedom to design the internal structure allow for nearly countless and yet to discover applications. To be able to test PCFs and use common equipment without costly customisation would require the splicing of PCFs to SMFs. This however gives rise to another issue. The holes within the PCF tend to collapse due to surface tension of molten glass during the hot splicing process where the glass is melted and fused together. The collapsed holes cause changes in desired properties and also cause signal transmission losses through leakage of light at splice points. This project will attempt to make use of a pressurised method to inject pressurised air into the fibre during splicing to reduce the collapse of the holes. A pressurisation apparatus attachment will be designed and made with the intention for it to an external attachment to any splicing machine. The project will also include familiarisation of splicing machines such as Fusion Arc Splicer and CO2 Laser Splicer. The Optical Spectrum Analyser will be used to measure the power transmission across the length of fibre before and after splicing to determine the splice loss. SMF to SMF, PCF to PCF, PCF to SMF and the pressurised process of splices involving PCF will be tested and optimised to investigate the viability and effectiveness of a pressurised splice. The learning process, methodology and results will be detailed in the following pages of this report.